Insight Into the Superlubricity and Self-Assembly of Liquid Crystals - Tan, Shanchao; Tao, Jiayu; Luo, Wendi; Shi, Hongyu; Tu, Bin; Jiang, Hao; Liu, Yuhong; Xu, Haijun; Zeng, Qingdao (Frontiers in Chemistry, 2021)
Liquid crystals are promising molecular materials in the application of lubrication. Herein, the microscale superlubricity is accomplished by the construction of uniform and ordered self-assembly of several liquid crystals. The self-assembly structures on a highly oriented pyrolytic graphite (HOPG) surface are explicitly revealed by using scanning tunneling microscopy (STM). Meanwhile, the nanotribological performance of the self-assemblies are measured by using atomic force microscopy (AFM), revealing ultralow friction coefficients lower than 0.01. The interaction energies are calculated by density functional theory (DFT) method, indicating the positive correlation between friction coefficients and interaction strength. The effort on the self-assembly and superlubricity of liquid crystals could enhance the understanding of the nanotribological mechanism and benefit the further application of liquid crystals as lubricants.